ORIGINAL ARTICLELeflunomide in treatment of RA patents preliminary estimation of therapeutical efficiency and side effects - Rell-Bakalarska, Maria; Jaworski, Janusz; Rutkowska-Sak, Lidia; Wieczorek, Małgorzata; Kwiatkowska, Małgorzata; Klimczak, Ewa; Kowalczuk, Bożena; Rell, Krzysztof Wojciech (Reumatologia/Rheumatology, 2006)
In the preliminary estimation there were studied efficiency and safety of therapy leflunomid in patients with RA. The drug was given p. o. to a group of 158 patients (150 females and 8 males) for 3 days 100 mg/24 h, and then again 20 mg/24 h. The age of patients varied between 19-78 (average age was 55 years), with average duration time of the disease 10 years and 2 months. All of the patients were previously unsuccessfully treated with other DMARDS. All of the patients had high activity of disease estimated by DAS 28 ≥5.1 61.4% of patients were treated with long-term glicocorticosteroids. Time of trial was scheduled for 6 months. The therapeutical effect was initially estimated on the basis of a group of 43 patients who took the medicine for 91-120 days. Good and average therapeutical efficiency of treatment was observed in 76.73% of patients. Efficiency was expressed by lowering DAS 28 by 0.6-1.2 in a group of 11.62% of patients and 1.2 in a group of 65.11% of patients. In a group of 3.79% of patients the treatment was stopped because of complete lack of therapeutical effect. Frequency of side effects was initially estimated in a group of 158 patients. Treatment was interrupted in the group of 8.86% of patients because of such side effects as: diarrheas, elevation of transaminazes, leukopenia and trombocytopenia, skin changes and dizziness. Observations are continued. Preliminary results of observations allow for positive evaluation of treatment with leflunomid in RA patients.